2011
DOI: 10.4081/uij.2011.e4
|View full text |Cite
|
Sign up to set email alerts
|

Low-count bacteriuria in refractory idiopathic detrusor overactivity versus controls

Abstract: Background. Previous studies suggest an association between idiopathic detrusor overactivity (IDO) and high-count bacteriuria (>105 CFU/mL). Recently, the importance of low-count bacteriuria (103–105 CFU/mL) in dysuric women with has been recognised. However, the optimal microbiological threshold for women with overactive bladder (OAB) symptoms remains unclear. Design and Methods A 2-year prospective cohort study, to examine the incidence of low-count and high-count bacteriur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…A study of midstream urine specimens from 50 refractory OAB women and 50 controls obtained positive urine cultures (≥ 10 3 CFU mL −1 ) from 39% of those with urge incontinence compared with 6% of controls ( P < 0.0001), with the majority of these UTI caused by E. coli , and associated pyuria (Walsh et al ., ). A later study of catheterized urine specimens from patients with newly diagnosed OAB revealed bacteriuria in 13%, the majority culturing E. coli with pyuria, vs. 6% of controls ( P = 0.07; Walsh et al ., ). Thus, it appears that in this subset of refractory OAB, up to one‐third of patients may exhibit bacterial cystitis, albeit without expression of the dysuria or foul‐smelling urine symptoms that have been considered the classic hallmarks of UTI.…”
Section: Some Urinary Tract Diseases Traditionally Considered ‘Noninfmentioning
confidence: 97%
See 1 more Smart Citation
“…A study of midstream urine specimens from 50 refractory OAB women and 50 controls obtained positive urine cultures (≥ 10 3 CFU mL −1 ) from 39% of those with urge incontinence compared with 6% of controls ( P < 0.0001), with the majority of these UTI caused by E. coli , and associated pyuria (Walsh et al ., ). A later study of catheterized urine specimens from patients with newly diagnosed OAB revealed bacteriuria in 13%, the majority culturing E. coli with pyuria, vs. 6% of controls ( P = 0.07; Walsh et al ., ). Thus, it appears that in this subset of refractory OAB, up to one‐third of patients may exhibit bacterial cystitis, albeit without expression of the dysuria or foul‐smelling urine symptoms that have been considered the classic hallmarks of UTI.…”
Section: Some Urinary Tract Diseases Traditionally Considered ‘Noninfmentioning
confidence: 97%
“…On the other hand, patients presenting with the main complaints of frequency/urgency/nocturia/urge incontinence without dysuria and bacteriuria (>10 5 CFU mL −1 ) are considered to have the OAB syndrome (Walsh & Moore, ). However, recent evidence has demonstrated pyuria (Horsley et al ., ) and low‐count (≥ 10 3 CFU mL −1 ) bacteriuria on catheter specimens in patients diagnosed with OAB (Walsh et al ., ; Walsh & Moore, ). Furthermore, recent evidence indicates that a portion of women with refractory OAB experience recurrent episodes of bacterial cystitis that manifest as acute exacerbations of the frequency/urgency/nocturia/urge incontinence symptoms, without the classical dysuria or foul‐smelling urine usually associated with bacteriuria.…”
Section: Some Urinary Tract Diseases Traditionally Considered ‘Noninfmentioning
confidence: 99%
“…If such patients are found to have two cultures of the same species 24 h apart, with bacteriuria ≥ 10 5 CFU mL −1 of uropathogens (Grabe et al ., ), in the absence of dysuria, controversy now exists as to whether such women should be considered as having ABU, or in fact, a sUTI that warrants treatment. Recent evidence indicates that 26% of women with severe OAB may have ≥ 10 5 CFU mL −1 without the classical features of dysuria or malodorous urine, compared with 4% of age‐matched continent controls (Walsh et al ., ). The role of urine leakage onto the perineum with possible facilitation of bacterial colonization of the urethral orifice remains controversial also, because patients with OAB leak urine intermittently, not continuously.…”
Section: Current Controversy: Etiology Of Bacteriuria In Women With Umentioning
confidence: 97%
“…We found that, in non‐dysuric women with “refractory” DO, the prevalence of bacteriuria≥10 3 CFU/ml, at a time of clinically worsened urgency symptoms, was 39% 3. Notably, only “low‐count” bacteriuria (10 3 –10 5 CFU/ml) was cultured in one‐third of positive cases in our study 3. This is pertinent as the importance of low bacterial counts in patients with lower urinary tract symptoms is increasingly recognized 4.…”
mentioning
confidence: 77%
“…The concept of “refractory” DO has not been well studied and no general consensus exists on the most appropriate definition 2. We previously reported a 2‐year prospective study on the prevalence of bacteriuria in women with “refractory” DO (defined as “ failure to respond to ≥ 2 anti‐cholinergic agents coupled with out‐patient bladder training for ≥ 1 year, with persistent disabling symptoms on frequency‐volume chart” ) during episodes of acute exacerbation of OAB symptoms 3. We found that, in non‐dysuric women with “refractory” DO, the prevalence of bacteriuria≥10 3 CFU/ml, at a time of clinically worsened urgency symptoms, was 39% 3.…”
mentioning
confidence: 99%